THE RESEARCH TECHNIQUES FOR ANALYSIS OF MECHANICAL AND TRIBOLOGICAL PROPERTIES OF COATING-SUBSTRATE SYSTEMS - Kinga CHRONOWSKA-PRZYWARA; Marcin KOT; Sławomir ZIMOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents research techniques for the analysis of both mechanical and tribological properties of thin coatings applied on highly loaded machine elements. In the Institute of Machine Design and Exploitation, AGH University of Science and Technology students of the second level of Mechanical Engineering study tribology attending laboratory class. Students learn on techniques for mechanical and tribological testing of thin, hard coatings deposited by PVD and CVD technologies. The program of laboratories contains micro-, nanohardness and Young's modulus measurements by instrumental indentations and analysys of coating to substrate adhesion by scratch testing. The tribological properties of the coating-substrate systems are studied using various techniques, mainly in point contact load conditions with ball-on-disc and block-on-ring tribomiters as well as using ball cratering method in strongly abrasive suspensions.